World History: The Middle Ages 1101-1460 - "Kingfisher"; Hazel Mary Martell (Kingfisher Books Ltd London, 1997)
Covers global history from 1101 to 1460 AD. Topics include the Crusades, the Black Death, the Ming Dynasty, and notable advancements in science and technology
As a Kingfisher publication, it's likely aimed at a younger or general-interest audience$1 (Baccessible and educational. No review ratings were found through the sources searched, suggesting it's more niche or less commonly reviewed commercially.s